Household preference for wastewater reuse/recycling practice determinants in a growing community in Nigeria - Ogunbode, Timothy O.; Oyebamiji, Victor O.; Ogundele, John A.; Faboro, Oluwatobi O. (Frontiers in Environmental Science, 2023)
Wastewater recycling has been considered as one of the ways of ensuring sustainable water accessibility for domestic purposes as being postulated against 2030 through Sustainable Development Goals (SDGs). This work investigated the factors which guide the preference for water recycling in Iwo, Osun State, Nigeria so as to encourage its practice in homes. A survey was conducted among randomly selected 205 respondents in the study area in order to generate the data required to achieve the objectives of the study. Both descriptive and inferential statistical analyses were used using SPSS version16.0. The study revealed that 79.3% of the respondents who were mostly women in homes claimed ‘nay’ against wastewater reuse, attributing this to good access to freshwater, among other reasons. The Factor Analysis (FA) of the 13 variables obtained from the field extracted 6 variables which gave 76.542% of the variance about the respondents’ preference for wastewater recycling namely: (i) Method of producing wastewater; (ii) Proportion of the wastewater available for use; (iii) volume of wastewater generated; (iv) Level of support for the practice of wastewater recycling; (v) perception about wastewater; and (vi) Reasons for wastewater recycling. Further analysis revealed that the 6 variables could be summarized into 2 with the first three factors forming the first and the last three variables forming the second group- issues related to wastewater production and human attitude-related factors. We, therefore, reject the alternative hypothesis (H1) and accept the null hypothesis (Ho) that availability of wastewater does not hinder households’ preference for its use. The work, therefore, concluded that the preference for wastewater recycling are associated with issues bothering on its production and human attitude/perception about wastewater. Public enlightenment and wastewater treatment technology in the study area and other similar communities could probably enhance the preference for wastewater recycling.